Characterizing Pelvic Floor Muscle Activity During Walking and Jogging in Continent Adults: A Cross-Sectional Study - Williams, Alison M. M.; Sato-Klemm, Maya; Deegan, Emily G.; Eginyan, Gevorg; Lam, Tania (Frontiers in Human Neuroscience, 2022)
Introduction: The pelvic floor muscles (PFM) are active during motor tasks that increase intra-abdominal pressure, but little is known about how the PFM respond to dynamic activities, such as gait. The purpose of this study was to characterize and compare PFM activity during walking and jogging in continent adults across the entire gait cycle. Methods: 17 able-bodied individuals (8 females) with no history of incontinence participated in this study. We recorded electromyography (EMG) from the abdominal muscles, gluteus maximus (GM), and PFM while participants performed attempted maximum voluntary contractions (aMVC) of all muscles and completed 60-70 strides in four gait conditions: slow walk (1 km/h); regular walk (self-selected comfortable pace); transition walk (self-selected fastest walking pace); jog (same speed as transition walking). We quantified activity throughout the whole gait cycle (%aMVCGC) and during periods of bursting (%aMVCBR) for each participant, and analyzed the timing of PFM bursting periods to explore when the PFM were most active in the gait cycle. We also conducted a phase metric analysis on the PFM and GM burst timings. We performed a Spearman’s rank-order correlation to examine the effect of speed on %aMVCGC, %aMVCBR, and phase metric score, and used the Wilcoxon Signed-Rank test to evaluate the effect of gait modality, matched for speed (walking vs. jogging), on these variables. Results: The PFM were active throughout the gait cycle, with bursts typically occurring during single-leg support. The PFM and GM were in phase for 44-69% of the gait cycle, depending on condition. There was a positive correlation between gait speed and both %aMVCGC and %aMVCBR (p < 0.001). Phase metric scores were significantly higher during jogging than transition walking (p = 0.005), but there was no difference between gait modality on %aMVCGC or %aMVCBR (p = 0.059). Where possible we disaggregated data by sex, although were unable to make statistical comparisons due to low sample sizes. Conclusion: The PFM are active during walking and jogging, with greater activity at faster speeds and with bursts in activity around single-leg support. The PFM and GM co-activate during gait, but are not completely in phase with each other.